Development of Fun Thinkers Book Media On Theme 9 subtheme 1 Wealth of Energy Sources in Energy Sources in Indonesia Class IV kuta pasie primary school - Fitriani; Musdiani; lala Septiona; Riza Oktariana; Liza Fidiawati; Rossiana Br Ginting; Tengku Hartati; Syarifah Salsabila (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research and development is motivated by students in class IV during theteaching and learning process in class, students still seem less interested inlearning as seen from their attention diverted such as chatting with friends,paying less attention to the teacher's explanation, students prefer to write,Teachers only use learning media such as whiteboards, student print books,without the presence of varied media. but the learning outcomes obtained areless than optimal and students also lack enthusiasm in learning. The purpose ofthis study was to produce fun thinkers book media and determine the level ofvalidation of fun thinker book media on the material of the wealth of energysources in Indonesia. The data collection techniques in this study wereobservation, validation, questionnaire, test (post-test and pre-test). The researchinstruments used in this study are validation sheets (media experts), validationsheets (material experts), validation sheets (linguists) questionnaires (teacherand student responses), test questions. The results of the development of funthinkers book media on the subtheme of the wealth of energy sources inIndonesia that have been developed in this study have very feasible results tobe used as teaching materials in the learning process. Based on the results ofproduct validation by validators obtained media expert validation 96% materialexpert validation 96% language expert validation 93% with the criteria